2017
DOI: 10.1093/carcin/bgx044
|View full text |Cite|
|
Sign up to set email alerts
|

Sulforaphane suppresses PRMT5/MEP50 function in epidermal squamous cell carcinoma leading to reduced tumor formation

Abstract: Protein arginine methyltransferase 5 (PRMT5) cooperates with methylosome protein 50 (MEP50) to arginine methylate histone H3 and H4 to silence gene expression, and increased PRMT5 activity is associated with enhanced cancer cell survival. We have studied the role of PRMT5 and MEP50 in epidermal squamous cell carcinoma. We show that knockdown of PRMT5 or MEP50 results in reduced H4R3me2s formation, and reduced cell proliferation, invasion, migration and tumor formation. We further show that treatment with sulfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 65 publications
1
22
3
Order By: Relevance
“…Proliferation of OPCs in vivo was not affected by loss of Prmt5 (Fig. 3d ) and this was in contrast with previous reports on the effect of PRMT5 inhibition in cancer cells 40 , 41 . To further ascertain that PRMT5 did not affect proliferation, we treated primary cultures of OPCs with GSK591, a selective inhibitor of PRMT5 (which inhibits symmetric dimethylation of arginine containing substrates by the PRMT5/MEP50 complex 42 ) (Fig.…”
Section: Resultscontrasting
confidence: 99%
“…Proliferation of OPCs in vivo was not affected by loss of Prmt5 (Fig. 3d ) and this was in contrast with previous reports on the effect of PRMT5 inhibition in cancer cells 40 , 41 . To further ascertain that PRMT5 did not affect proliferation, we treated primary cultures of OPCs with GSK591, a selective inhibitor of PRMT5 (which inhibits symmetric dimethylation of arginine containing substrates by the PRMT5/MEP50 complex 42 ) (Fig.…”
Section: Resultscontrasting
confidence: 99%
“…We further detected the expression of NF-κBp65 protein in tumor tissues of nude mice, finding that injecting si-PRMT5+Si-LXRα for co-transfection could reverse the expression of LXRα protein and NF-κBp65 protein in tumor tissues of nude mice injected with si-PRMT5. A previous study also suggested that inhibition of PRMT5 could suppress the growth of tumors in vivo, 31 which further confirmed our conjecture.…”
Section: Discussionsupporting
confidence: 90%
“…To our knowledge, this is the first study to report such a correlation and our results further highlight the importance of PRMT5 as a potential HCC biomarker. In addition to in vivo studies, several in vitro experiments have revealed that depletion of PRMT5 induced a decrease in cancer cell survival (36) and proliferation (19,28,34,(36)(37)(38). While these phenotypes have been observed in various cancer cell lines, the exact molecular mechanisms remain to be established.…”
Section: Discussionmentioning
confidence: 99%
“…These results were in accordance with the previous finding that the depletion of PRMT5 modulated the expression of E-cadherin through interactions with Ajuba, to regulate the transcription factor Snail (6). However, earlier invasion analyses were performed under conditions whereby the PRMT5 siRNAs used induced a decrease in cell proliferation and/or survival (17,18,38). Decreased proliferation and survival can affect the invasion of cancer cells, thus reducing cell activity.…”
Section: Discussionmentioning
confidence: 99%